Decitabine and SAHA-induced apoptosis is accompanied by survivin downregulation and potentiated by ATRA in p53-deficient cells - Brodská, Barbora; Otevřelová, Petra; Holoubek, Aleš (Oxidative medicine and cellular longevity, 2014)
While p53-dependent apoptosis is triggered by combination of methyltransferase inhibitor decitabine (DAC) and histone deacetylase inhibitor suberoylanilide hydroxamic acid (SAHA) in leukemic cell line CML-T1, reactive oxygen species (ROS) generation as well as survivin and Bcl-2 deregulation participated in DAC + SAHA-induced apoptosis in p53-deficient HL-60 cell line. Moreover, decrease of survivin expression level is accompanied by its delocalization from centromere-related position in mitotic cells suggesting that both antiapoptotic and cell cycle regulation roles of survivin are affected by DAC + SAHA action. Addition of subtoxic concentration of all-trans-retinoic acid (ATRA) increases the efficiency of DAC + SAHA combination on viability, apoptosis induction, and ROS generation in HL-60 cells but has no effect in CML-T1 cell line. Peripheral blood lymphocytes from healthy donors showed no damage induced by DAC + SAHA + ATRA combination. Therefore, combination of ATRA with DAC and SAHA represents promising tool for therapy of leukemic disease with nonfunctional p53 signalization.
Keywords: Tumor Suppressor Protein p53; kontrolní body M fáze buněčného cyklu; apoptóza; HL-60 buňky; Antimetabolites, Antineoplastic; Decitabine; lymfocyty; azacytidin; Cell Line, Tumor; Tretinoin; decitabin; Apoptosis; tretinoin; vorinostat; M Phase Cell Cycle Checkpoints; Vorinostat; lidé; Reactive Oxygen Species; Azacitidine; HL-60 Cells; Hydroxamic Acids; kyseliny hydroxamové; Down-Regulation; survivin; Drug Synergism; protinádorové antimetabolity; nádorový supresorový protein p53; G2 Phase Cell Cycle Checkpoints; reaktivní formy kyslíku; synergismus léků; Lymphocytes; inhibitory apoptózy; down regulace; Survivin; kontrolní body fáze G2 buněčného cyklu; nádorové buněčné linie; Inhibitor of Apoptosis Proteins; Humans